PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENGEMBANGAN APLIKASI MOBILE MENGGUNAKAN APP INVENTOR KELAS XI-G DI SMAN 1 TRENGGALEK TAHUN AJARAN 2025/2026 SEMESTER 2 - Fathurrohman; Vertika Panggayuh; Fahrur Rozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of Grade XI-G students in Informatics on Mobile Application Development Using App Inventor, with a class average of 70.89 and classical mastery of only 25% out of 36 students against a mastery criterion (KKTP) of 78. This study aimed to improve student learning outcomes through the implementation of the Problem Based Learning (PBL) model. This research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, each comprising planning, acting, observing, and reflecting. The subjects were 36 Phase F students of Grade XI-G at SMA Negeri 1 Trenggalek, divided into 6 heterogeneous groups. Data were collected through observation, tests, interviews, and documentation, then analyzed quantitatively and qualitatively, with a success indicator of at least 85% classical mastery. Results showed the class average increased from 73.75 in the pre-cycle to 77.92 in Cycle I and 82.31 in Cycle II; classical mastery increased from 27.78% to 58.33%, reaching 80.56% in Cycle II. Although the 85% target was not fully met, the improvements were significant across cognitive, psychomotor, and affective aspects, demonstrating that the Problem Based Learning model is effective in improving student learning outcomes on this material.